Monetary and Exchange Rate Policies in an Open Economy the Malaysian Case, 1959-1992 (Malaysian Management Journal, 1995)
The main purpose of this paper is to analyse the role of the exchange rate and monetary policy in a small open economy and to discuss the interaction of these policies in the Malaysian context. The Malaysian experience indicates that there is a close interaction and sometimes a trade-off, between monetary and exchange rate policies. The experience of Malaysia, particularly in 1992, underscores the need to view stabilisation policies in their totality within the proper perspective. Both exchange rate and monetary policies must be seen as part and parcel of an integrated package of macroeconomic measures. In addition, there is a need for co-operative actions across the full range of policies, both domestically and across countries, in order to promote stable longÂterm economic developments.